Economic polarisation in Europe: Causes and policy options - Jakob Kapeller; Claudius Gräbner; Philipp Heimberger (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2019)
This study discusses the challenges economic policy-makers in Europe have to cope with in order to ensure an economically prosperous and institutionally stable community of Member States of the European Union (EU). At the analytical level, we not only document a process of multi-dimensional polarisation of EU countries, but also link the existing economic divergences with a central long-term problem, namely structural polarisation: differences in the institutional and legal embedding (e.g. in the areas of tax and corporate law, the labour market or the financial sector) and technological capabilities are a major driver of divergence in living standards between some Member States. This polarisation, which started already before the financial crisis but has intensified over the last ten years, is largely due to the global as well as European "race for the best location". Without coordinated and cooperative intervention by economic policy-makers, a further drifting apart of economic development paths seems unavoidable. The large differences in the production structures of the EU countries and the resulting highly unequal distribution of technological capabilities are self-reinforcing in nature and would further intensify polarisation. The present study provides proposals for a coherent European overall strategy that not only addresses existing problems and makes possible the often-promised upward convergence between EU countries. It also provides a potential basis for dealing with key future challenges (such as digitisation, ageing society, climate change or global trade) on the basis of common European objectives. The focus is on safeguarding and expanding European values and institutions in order to deepen European integration at key points and thus to contribute, in the medium to long run, also to a transformation of the global economic order from the European side. A central argument is that coordinated measures in various policy areas - especially in wage, monetary, fiscal and industrial policy - are of central importance in order to create a long-term successful economic basis for the common European economic and monetary area.
Keywords: B5; F6; F45; 330; Europe; European integration; economic openness; competitiveness